Systematic Literature Review (SLR) Implementasi Akad Mudharabah dalam Perekonomian di Indonesia - Dwi Lestari; Elvi Khairani Sofyan; Rambe Roisuddin Ery; Sulhi; Anzu Elvia Zahara (STEKOM PRESS, 2023)
This study aims to conduct a literature review of the results of research on the Implementation of Mudharabah Agreements in the Economy in Indonesia. This study uses a Systematic Literature Review (SLR) with a qualitative approach. The results of this study indicate that based on the results of the Systematic Literature Review, it shows that the mudharabah contract is one of the pillars of the sharia economy that represents Islamic principles to realize social justice through a profit-sharing system. As well as the implementation of the mudharabah contract in the Indonesian economy is in accordance with maqasyid sharia which is able to encourage the welfare of the people. This research method uses the Systematic Literature Review (SLR) method using a qualitative descriptive approach.